3D Printing High‐Resolution Conductive Elastomeric Structures with a Solid Particle‐Free Emulsion Ink. Issue 3 (18th August 2021) - Wang, Chen; Chaudhary, Gaurav; Ewoldt, Randy H.; Nuzzo, Ralph G.
Abstract : Fabricating complex structures on micro‐ and mesoscales is a critical aspect in the design of advanced sensors and soft electronics. However, soft lithographic methods offer an important approach to fabricating such structures, the progress in the field of additive manufacturing (e.g., 3D printing) offers methods of fabrication with much more material complexity. The rheological complexity of the printing material, however, often dictates the limitations of printing. In particular, the challenges involved in synthesizing printing materials that can enable shape retention at smaller scales (<100 μm), yet be conductive, limits many applications of 3D printing to soft microelectronics. Herein, a printing‐centered approach using a novel particle‐free conductive emulsion ink is presented. This approach separates the printing and polymerization of a conductive monomer (pyrrole) and renders a novel ink that is used to print filaments with heretofore impossible to realize 3D feature dimensions and build structures with high shape retention. The printability of the ink is evaluated, and post‐treatment properties assessed. Multidirectional strain sensors are printed using the emulsion ink to illustrate an exemplary application in soft electronics. Abstract : Electrically conductive elastomeric structures are 3D printed with a hard particle‐free emulsion ink. The microstructure and the rheological properties of ink allows for feasible fabrication of 3D structures using tips as small as 10 μm. A multipurpose strain sensor is fabricated to demonstrate the strain‐dependent conductivity of the printed structure.